Determination of Quality Skin Care for Children with Burns Injuries in Baghdad City Hospitals - Ali O. Al-sudani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aims: This study was conducted to the determine quality nursing skin care about child with burn injuries.Methodology: Results A descriptive study design was carried out at the non Teaching Hospitals in BaghdadCity from the August 27th of 2020up to the 20th of November 2020.The study aims to determine the qualityof nursing care to provide the child with burns injury at burn units .Non probability (purposive) sample of(70) nurses were selected from burns wards in non Teaching Hospitals in Baghdad City, and they have atlast one year of experience in burn units. The study instruments consisted of four major parts which wereconstructed for the purpose of the study. First part related to nurses demographic data, the second partrelated to nurse’s practices about part concerning skin care of observational checklist and composed of (16)items. The data were collected through the using of constructed questionnaire which consists of (16) itemsand filled by using observational checklist, data analyzed by using two statistical approaches: descriptivestatistical analysis frequencies, percentage, range of scores, mean of scores, and inferential statistical analysis(correlation coefficient and chi- square test). In addition (37.1%) of the sample have acceptable scores relatedto skin care provided to child with burns at burn units. Moreover, the findings also reflects that no significantrelationship between nurse’s practices and their age, gender, monthly income, number of training sessionsand place of training. However , significant relationship is found between their practices and the nurses’level of education, and training session.Results: table (1) shows (44.3%) of the sample (20-29) years old ,(71.4%) were male, (52.9%) were graduatefrom institute of nursing ,(70.0%) their monthly income was not enough , (71.4%) of the sample have lessthan 5 years of experience in burn units ,(52.9%) have training sessions related to child’s burn care , 22(59.5%) of sample have one training sessions and place of training in burn care,19 (51.4%) trained outsideof Iraq..The finding of this table and figure indicated that (26) (37.1%) of nurses provide good skin care, (26)(37.1%) did the care in acceptable level and (18) (25.7%)was in poor level figure 1.